PENGEMBANGAN MODUL TARI KOLABORATIF UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN PEMAHAMAN LITERASI BUDAYA SEKOLAH INOVASI METROPOLIS - Nugrohaji, Adheari Sya’ban; Muhsin, Achmad Mukhalis; Husna, Alya Putri Afifathul (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
This study aims to develop a collaboration-based Rampak Dance learning module to improve cultural literacy and social skills of elementary school students. The research approach used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which is carried out systematically from needs analysis to evaluation of module effectiveness. The study population included fourth and fifth grade students of SD Negeri Durung Banjar Candi Sidoarjo, with a sample of 30 students selected through purposive sampling technique. Data were obtained through observation, interviews, questionnaires, and documentation, which were then analyzed qualitatively and quantitatively. The results showed that the module was effective in improving students' understanding of local cultural values, with the average score of the questionnaire increasing from 60 to 92. In addition, students' social skills also improved significantly, as evidenced through statistical analysis using t test (p < 0.05). Teachers gave positive feedback on the implementation of this module, stating that the project-based method applied successfully increased student motivation and facilitated interactive learning. This study concludes that the ADDIE-based module is not only relevant to improve the quality of cultural arts learning at SD Negeri Durung Banjar Candi Sidoarjo, but can also be an innovative learning model for other schools with similar needs